Relationship of coping strategies with resilience, self-efficiency, and anxiety in the new normal period of the covid-19 pandemic on Teenagers In Kupang City - Antonia Helena Hamu; Sabinus Bunga Ama Kedang; Antonius Rino Vanchapo (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The COVID-19 pandemic has caused everyone to feel anxious. The government has made several preventive strategies to inhibit the spread of the virus through social distancing, physical distancing, and the stay at home order which lead to the decreasing access to family, friends, and other social support systems and causing loneliness and increasing psychological problems such as anxiety and depression. Thus, everyone, especially teenagers, are expected to be able to adapt to the new habits (the new normal) in carrying out healthy and clean-living behaviour. Those who are prone to COVID-19 gradually develop adaptive and functional skills and competencies, and build a self-identity that can prepare themselves to carry out their roles and respond to societal expectations as they mature, which can also be regarded as a period of storms and stress. Objectives: Is to identify the relationship of coping strategies with resilience and anxiety in the transition to the new normal during the COVID-19 pandemic on teenagers in Kupang City. Methods: The research design used in this study was cross-sectional. The sample in this study was 147 measured using the inclusion and exclusion criteria that had been set. Meanwhile, the inclusion criteria in this study were as follows: domiciled in Kupang City, have stayed in Kupang for more than 3 years, aged over 15-19, and class VII of junior high school. The measuring instrument used in this study is the Ways of Coping questionnaire from Folkman to measure coping strategies, the self-rating anxiety scale (SRAS) questionnaire from Zung to measure anxiety, and the Gartland Questionnaire to measure resilience. The data analysis was conducted by using Chi Square test. Results:The results showed p-value < 0.05 was a relationship of coping strategies with self-efficacy and anxiety on junior high school teenagers in Kupang City. Conclusions: Coping strategies have a very significant relationship with self-efficacy and anxiety in adolescents. Adolescents who have good coping strategies have good self-efficacy during the new normal era. This is also similar to anxiety, adolescents who have good coping strategies have low anxiety.